Phosphorus Acquisition Efficiency Related to Root Traits: Is Mycorrhizal Symbiosis a Key Factor to Wheat and Barley Cropping? - Campos, Pedro; Borie, Fernando; Cornejo, Pablo; López-Ráez, Juan A.; López-García, Álvaro; Seguel, Alex (Frontiers in Plant Science, 2018)
Wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) are major crops cultivated around the world, thus playing a crucial role on human diet. Remarkably, the growing human population requires a significant increase in agricultural production in order to feed everybody. In this context, phosphorus (P) management is a key factor as it is component of organic molecules such as nucleic acids, ATP and phospholipids, and it is the most abundant macronutrient in biomass after nitrogen (N), although being one of the scarcest elements in the lithosphere. In general, P fertilization has low efficiency, as only a fraction of the applied P is acquired by roots, leaving a substantial amount to be accumulated in soil as not readily available P. Breeding for P-efficient cultivars is a relatively low cost alternative and can be done through two mechanisms: i) improving P use efficiency (PUE), and/or ii) P acquisition efficiency (PAE). PUE is related to the internal allocation/mobilization of P, and is usually represented by the amount of P accumulated per biomass. PAE relies on roots ability to acquire P from the soil, and is commonly expressed as the relative difference of P acquired under low and high P availability conditions. In this review, plant adaptations related to improved PAE are described, with emphasis on arbuscular mycorrhizal (AM) symbiosis, which is generally accepted to enhance plant P acquisition. A state of the art (1980 to 2018) of AM growth responses and P uptake in wheat and barley is made to discuss about the commonly accepted growth promoting effect and P increased uptake by AM fungi and the contrasting evidence about the generally accepted lack of positive responses in both plant species. Finally, the mechanisms by which AM symbiosis can affect wheat and barley PAE are discussed, highlighting the importance of considering AM functional diversity on future studies and the necessity to improve PAE definition by considering the carbon trading between all the directly related PAE traits and its return to the host plant.